INTERACTION OF MARKETING AND LOGISTICS AT STAGES OF LIFE CYCLE OF PRODUCTS - K. Igrokova (Вестник университета, 2016)
The arguments proving necessity of interaction of marketing and logistics departments at stages of the life cycle of goods (LCG) are presented. The modern evaluation treatment connecting marketing and logistics of each stage of LCG is given. The carrying out of evaluation purposes both logistics and marketing for the efficiency of their interaction.The marketing and logistics functions are discussed. These functions are concretized towards all stages of the life cycle of goods. Communication management efficiency with competent interactions of services of marketing and logistics is tracked.